Facile preparation of partially reduced graphite oxide nanosheets as a binder-free electrode for supercapacitors. Issue 51 (14th August 2018) - Zhang, Juncai; Deng, Lingjuan; Liu, Zong-huai
Abstract : Partial reduced graphite oxide nanosheets with excellent capacitive property have been prepared using commercial Cu2 O powders as reduction agent. Abstract : Preparation of graphene (GR) based electrode materials with excellent capacitive properties is of great importance to supercapacitors. Herein, we report a facile approach to prepare partially reduced graphite oxide (PRG) nanosheets by reducing graphite oxide (GO) using commercial Cu2 O powder as a reduction agent, moreover, we demonstrate that the PRG nanosheets can act as building blocks for assembling hydrogels (PRGH) and flexible film (PRGF). The obtained PRGH and PRGF can be directly used as binder-free electrodes for supercapacitors and give high specific capacitance (292 and 273 F g −1 at a current density of 0.5 A g −1 in a three-electrode system, respectively) due to the existence of oxygen-containing functional groups in PRG nanosheets. PRG also gives excellent rate ability and cycle stability. This study suggests a facile pathway to produce GR-based materials with excellent capacitive properties and is meaningful for flexible supercapacitors.